FMRP-Driven Neuropathology in Autistic Spectrum Disorder and Alzheimer's disease: A Losing Game - Bleuzé, Louis; Triaca, Viviana; Borreca, Antonella (Frontiers in Molecular Biosciences, 2021)
Fragile X mental retardation protein (FMRP) is an RNA binding protein (RBP) whose absence is essentially associated to Fragile X Syndrome (FXS). As an RNA Binding Protein (RBP), FMRP is able to bind and recognize different RNA structures and the control of specific mRNAs is important for neuronal synaptic plasticity. Perturbations of this pathway have been associated with the autistic spectrum. One of the FMRP partners is the APP mRNA, the main protagonist of Alzheimer’s disease (AD), thereby regulating its protein level and metabolism. Therefore FMRP is associated to two neurodevelopmental and age-related degenerative conditions, respectively FXS and AD. Although these pathologies are characterized by different features, they have been reported to share a number of common molecular and cellular players. The aim of this review is to describe the double-edged sword of FMRP in autism and AD, possibly allowing the elucidation of key shared underlying mechanisms and neuronal circuits. As an RBP, FMRP is able to regulate APP expression promoting the production of amyloid β fragments. Indeed, FXS patients show an increase of amyloid β load, typical of other neurological disorders, such as AD, Down syndrome, Parkinson’s Disease, etc. Beyond APP dysmetabolism, the two neurodegenerative conditions share molecular targets, brain circuits and related cognitive deficits. In this review, we will point out the potential common neuropathological pattern which needs to be addressed and we will hopefully contribute to clarifying the complex phenotype of these two neurorological disorders, in order to pave the way for a novel, common disease-modifying therapy.